Coping during socio-political uncertainty - El Khoury-Malhame, Myriam; Bou Malhab, Sandrella; Chaaya, Roni; Sfeir, Michel; El Khoury, Samar (Frontiers in Psychiatry, 2024)
Introduction: Well-being of young adults is known to be compromised in times of significant changes, such as economic and political turmoil. This study focuses on university students in Lebanon during one of the most prominent social unrests of its modern history to determine potential understudied protective factors that would predict the youth capacity to strive. Methods: A sample of 489 university students were asked to fill an online survey including standardized questionnaires of wellbeing (WEMWBS), depression (PHQ-9), anxiety (HAM-A), intolerance of uncertainty (IUS-12), coping (Brief COPE) in addition to demographics and questions about their attitudes and future perspectives. Results: We found increased rates of mental distress, predominantly in women, with around 80% of the sample being highly intolerant to the uncertainty climate. Results unsurprisingly show that wellbeing negatively correlated with anxiety, depression and intolerance of uncertainty. Overall, mental distress was found to mediate the relation between uncertainty and wellbeing, and the relation between maladaptive coping and wellbeing. Students who were intolerant of uncertainty and who used maladaptive coping strategies were more likely develop anxiety and depression and subsequently report poorer wellbeing. Conversely, having adaptive strategies was directly linked to higher well-being. Discussion: In spite of increased distress, some university students managed to preserve their wellbeing within a climate of severe socio-political uprise. These findings suggest that modifying subjective experience of events and using soft skillset could alleviate young adults' emotional distress in unstable societies.